Human liver‐derived CXCR6+ NK cells are predominantly educated through NKG2A and show reduced cytokine production. Issue 6 (19th February 2019) - Lunemann, Sebastian; Langeneckert, Annika E.; Martrus, Gloria; Hess, Leonard U.; Salzberger, Wilhelm; Ziegler, Annerose E.; Löbl, Sebastian M.; Poch, Tobias; Ravichandran, Gevitha; Sauter, Jürgen; Schmidt, Alexander H.; Schramm, Christoph; et al.
Abstract: NK cells have been implicated to affect the outcome of numerous liver diseases. In particular, members of the killer‐cell Ig‐like receptor (KIR) family, predominantly expressed by NK cells, have been associated with the outcome of hepatitis C virus infection and clearance of hepatocellular carcinoma. Inhibitory KIRs tune NK cell function through interaction with HLA class I, a process termed education. Nevertheless, the impact of the hepatic environment on NK cell education is incompletely understood. Therefore, we investigated the composition and function of hepatic KIR‐expressing NK cells. Matched PBMC and hepatic lymphocytes were isolated from 20 individuals undergoing liver surgery and subsequently phenotypically analyzed for expression of KIRs and markers for tissue residency using flow cytometry. NK cell function was determined by co‐culturing NK cells with the target cell line 721.221 and subsequent assessment of CD107a, IFN‐γ, and TNF‐α expression. Liver‐resident CXCR6 + /CD56 Bright NK cells lacked KIRs and were predominantly educated through NKG2A, while CXCR6 − /CD16 + NK cells expressed KIRs and resembled peripheral blood NK cells. Hepatic NK cells showed lower response rates compared to peripheral blood NK cells; in particular, CXCR6 + NK cells were hyporesponsive to stimulation with target cells. The high proportion of educated NK cells in both subsets indicates the importance of self‐inhibitory receptors for the balance between maintenance of self‐tolerance and functional readiness. However, the reduced functionality of hepatic NK cells may reflect the impact of the tolerogenic hepatic environment on NK cells irrespective of NK cell education. Abstract : Reduced functionality of hepatic NK cells may reflect the impact of the tolerogenic hepatic environment on NK cells irrespective of NK cell education.